2017
DOI: 10.1016/j.jacep.2017.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Experience With the Subcutaneous Implantable Cardioverter-Defibrillator in Teenagers and Young Adults

Abstract: Young patients may be suitable candidates for S-ICD because of the high number of lead failures with transvenous systems expected in these patients during their lifetime. In the present study, S-ICD therapy was safe and feasible in teenagers and young adults. However, episodes of inappropriate shocks may occur, but rates of inappropriate shocks were comparable to those in patients with transvenous ICDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…Eight studies ( N = 1726) reported information on inappropriate shocks at different follow‐up times . Overall no differences in rates of inappropriate shocks were found in the meta‐analysis (OR = 1.28; 95% CI: 0.91, 1.78).…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Eight studies ( N = 1726) reported information on inappropriate shocks at different follow‐up times . Overall no differences in rates of inappropriate shocks were found in the meta‐analysis (OR = 1.28; 95% CI: 0.91, 1.78).…”
Section: Resultsmentioning
confidence: 95%
“…Four studies ( N = 520) reported the number of patients with device removal . No difference was found between groups in the meta‐analysis (OR = 1.64; 95% CI: 0.40, 6.70).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations